Encyclopedia of distance learning - Howard, Caroline (Hershey, PA : Idea Group Reference, 2005)
'This encyclopedia offers the most comprehensive coverage of the issues, concepts, trends, and technologies of distance learning. More than 450 international contributors from over 50 countries'--Provided by publisher
Includes bibliographical references and indexes
Keywords: Distance education -- Encyclopedias